PERUBAHAN SOSIAL EKONOMI PEKERJA SEKS KOMERSIAL REMAJA DI PANTI PELAYANAN SOSIAL WANITA “WANODYATAMA” SURAKARTA - Dewi Saraswati; Rahesli Humsona (Journal of Development and Social Change, 2020)
This study aims to describe the social economic changes of teenage prostitution. This research was conducted at the "Wanodyatama" Women's Social Services Institution Surakarta because most of the rehabilitated women were teenagers. The theory used is the theory of social practice according to Bourdieu. This type of research is a qualitative descriptive study by the phenomenological method, where a type of research that seeks to describe the socio-economic changes of teenagers prostitution. Sources of data in this study are primary and secondary. Data collection techniques were carried out by means of observation, interviews and documents. Sources of data obtained using purposive sampling technique. The validity data to use data triangulation. The data analysis technique used is an interactive analysis model developed by Miles and Huberman. The results of research that contain facts about teenagers who become prostitute have several factors that habitus, capital and realm. Social changes that occur are changes in the person, social structure, structural functions, relations between different structures, and the emergence of new structures. In addition there are also four components of economic change attended by informants, namely education, social status, income, and income contribution. During the reform of the rehabilitation process at Institution with the approval of the entire set of processes and guidance provided, informants shifted the change in a positive direction because it showed the relationship of services and social improvements intended for prostitute was very useful and beneficial. Self-esteem, self-confidence, social responsibility in carrying out social tasks and most importantly can realize work that has been done is a community disease that must be overcome because work can damage the morale of nation.